25 Years of Community Forestry in Nepal: A Review of Fourth National Workshop Proceedings (Journal of Forest and Livelihood, 2005)
The purpose of this note is to summarize important points contained in the 587 pages long proceedings of the workshop, which comprises of 82 papers. While the papers are organized in four categories (keynote papers, sustainable forest management, livelihood and governance), large numbers of papers within each of these categories preclude readers to easily trace papers relevant to more specific aspects of community forestry. In this context, this note is prepared to both highlight one or two key points of each of the papers and guide the readers through the relevant sections in the proceeding. For space related reasons, citations of authors and bibliography have been avoided and page numbers of the respective articles are given in brackets immediately after the “key point (s)”.